Environment and urinary bladder cancer. A historical perspective - Nesi, Gabriella; Galli, Ilaria C.; Amorosi, Andrea; Santi, Raffaella (Polish Journal of Pathology, 2019)
Our understanding of aetiological factors associated with urinary bladder cancer has radically improved over the last decades. Cigarette smoking is considered the most important risk factor, even in the industrialised world, while various occupational and environmental exposures to chemicals are also held responsible. The link between bladder cancer and schistosomiasis, highly prevalent in sub-Saharan Africa, Sudan, Egypt, and Yemen, provides input for investigating and potentially preventing bladder carcinogenesis. Growing concern regarding environmental diseases prompts investigation into the historical milestones that have helped disentangle the relationships between health and environment.